Driving ecotourism loyalty through destination image, satisfaction and motivation - Rahayu, Sri; Vedy, Nabila Kharimah; Gumanti, Miswan (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2023)
Tourism, especially ecotourism, is a sector that plays a role in contributing to the Indonesian economy, especially finance and foreign exchange. However, the Covid-19 pandemic has affected this sector. Efforts to revive the ecotourism sector continue to be encouraged after the Pandemic. Padang Savana is one of the Ecotourism Sites that was affected by Covid-19 and was closed. Efforts continue to be made so that these ecotourism sites can rise and return to the interest of visitors. Efforts are being made to increase visiting loyalty through enhancing destination image, tourist motivation, travel satisfaction, and experience. The purpose of this study was to examine the effect of destination image, tourist motivation, travel satisfaction, and experience on ecotourism destination loyalty. This research approach uses a quantitative approach. The population and sample of this study were visitors to the Padang Savana ecotourism. Purposive Sampling was used as a sampling technique. Sources of data were obtained through surveys, and the results were processed using SEM PLS. The results of the study show that destination image and motivation have a positive and significant impact on travel satisfaction. Travel motivation and satisfaction affect destination loyalty. The results of this study are expected to be useful for ecotourism management to increase visitor loyalty through trip motivation and satisfaction. For future research research can be re-tested with different ecotourism sites and test hypotheses that have not been supported.